Religious Moderation in Paguyuban Mejing Tabon's Local Wisdom as Support for Accomplishing SDGs - Aridlah Sendy Robikhah; Azza Abidatin Bettaliyah; Arindah Oktavianti (Edumaspul: Jurnal Pendidikan, 2024)
The Paguyuban Mejing Tabon citizens are people who have diverse religious backgrounds. Local wisdom which contains the values of religious moderation is an important factor in harmony between residents, so that social conflict can be avoided. This is in line with the SDGs concept of the United Nations where there are pillars that focus on Social Development, namely promoting peace and justice. Therefore, this research aims to explain the local wisdom that exists in the Mejing Tabon Community, reveal the correlation between local wisdom and the values of religious moderation and explain the contribution of local wisdom to achieving the UN SDGs. This research is important to emphasize the importance of preserving local wisdom and implementing the values of religious moderation to avoid conflicts based on religious differences. So that it becomes a form of contribution to achieving the SDGs. This research uses qualitative methods with a sociological approach. The results of this research are 4 indicators of religious moderation, including National Commitment, Tolerance, Anti-Radicalism, and Local Cultural Accommodation. The application of religious moderation in the local wisdom of the Tabon Mejing Community Association includes: the Tabon Mejing Association Logo Contains National Commitment; Tolerance in Interfaith Prayer Activities at Religious Celebrations; Mejing Tabon's philosophy of Rawuh, Lungguh, and Aruh as an effort to ward off radicalism; and Gagrak Ngayogyakarta Clothing as a form of accommodation to local culture.